ANALYSIS OF THE ROLE OF CHARACTER EDUCATION IN PREVENTING DELINQUENCY IN CLASS V STUDENTS AT UPT SPF SDN DAYA II MAKASSAR - Munirah H; Ince Prabu Setiawan Bakar; Erwin Nurdiansyah (Media Inovasi Pendidikan dan Publikasi, 2023)
This research aims to find out how effective the role of character education is in preventing student delinquency at Upt. SDN Daya II Makassar. The method used in this research is a descriptive qualitative research method where data collection is carried out by means of interviews, observation and documentation of activities in the field. The data taken in this research comes from interviews with teaching staff at Upt. SDN Daya II Makassar and teaching staff, observing learning activities, and reviewing school documentation. The results of this research show that the implementation of character education in the classroom at SDN Daya II Makassar is integrated into learning which goes through three stages, namely the planning stage, the learning implementation stage and the learning evaluation stage. Strengthening character education is also carried out through habituation and example by teachers to students. According to the observation results, the implementation of character education is good at SDN Daya II Makassar. Meanwhile, student behavior is also good, this can be seen from the percentage of observation results that show good figures. Character education can help improve student behavior through habituation and example by teachers to students.